The physical measurement of bone - Njeh, Christopher F.; Langton, C. M. (Christian M.) (Series in medical physics and biomedical engineering, 2004)
"This book will be essential reading for scientists, medical physicists and engineers involved with bone related diseases, who need to know more about the various physical measurement techniques available to them. Equally, the broad coverage will provide a valuable introductory framework for students of medical physics and biomedical engineering"--BOOK JACKET.